CAF‐derived exosomes transmitted Gremlin‐1 promotes cancer progression and decreases the sensitivity of hepatoma cells to sorafenib - Qin, Wei; Wang, Li; Tian, Huan; Wu, Xiaocai; Xiao, Cuicui; Pan, Yuhang; Fan, Mingming; Tai, Yan; Liu, Wei; Zhang, Qi; Yang, Yang (Molecular carcinogenesis, 2022)
Hepatocellular carcinoma (HCC) is one of the most lethal malignancies worldwide because of metastasis. An increasing number of studies have reported that cancer‐associated fibroblasts (CAFs) have emerged as the largest component of the stroma and play a critical role in tumor‐promoting processes. However, the effects of CAFs on cancer progression and the sensitivity of hepatoma cells to sorafenib are not well characterized. Here, we identified the proteome of CAF‐derived exosomes, and unveiled that exosomal Gremlin‐1 derived from CAFs contributes to epithelial–mesenchymal transition (EMT) of hepatoma cells and the decrease of the sorafenib sensitivity through regulating Wnt/β‐catenin and BMP signaling pathways. Compared to control subjects, the level of plasma exosomal Gremlin‐1 was significantly increased in HCC patients. Further studies indicated that plasma exosomal Gremlin‐1 may predict sorafenib response in HCC patients. Collectively, our findings uncover CAFs‐derived Gremlin‐1‐rich exosomes promote EMT and decrease the sensitivity of hepatoma cells to sorafenib by Wnt/β‐catenin and BMP signaling.